The integration of music and mathematics education in Catalonia and England: perspectives on theory and practice. (1st January 2018) - Viladot, Laia; Hilton, Caroline; Casals, Albert; Saunders, Jo; Carrillo, Carmen; Henley, Jennie; González-Martín, Cristina; Prat, Montserrat; Welch, Graham
ABSTRACT: The relationship between music and mathematics has often been the subject of discussion, both inside and outside the field of education. As part of an exciting project on a European scale, the paper explores the changing contexts in Catalonia (Spain) and England (UK) in relation to the integrated approach to the teaching of music and mathematics. We analyse three areas: academic literature, the curriculum frameworks and publications and resources prepared by and for teachers. Our findings suggest that due to the more favourable attitude towards cross-curricular approaches in education, more progress has been made in England, in terms of developing resources to support an integrated approach to the teaching of music and mathematics, than in Catalonia. Nonetheless, teachers in both locations are very interested in developing these approaches. Although there is a need for further teacher training and support, there is evidence of progress already being made in schools.